Outbreak Investigation and Enhanced Contact Tracing of Novel Coronavirus Disease 2019 (COVID-19), Ablekuma North Municipality, Greater Accra, Ghana - Anthony Baffour Appiah; Benedict Calys-Tagoe; Gyesi Razak Issahaku; Delia Akosua Bandoh; Charles Lwanga Noora; Samuel Dapaa; Charlotte-Alberta Cato; Donne Kofi Ameme; Ernest Kenu (Journal of Interventional Epidemiology and Public Health)
Introduction: After Ghana recorded its first two cases of COVID-19, other cases were subsequently identified in other parts of the country. The Ablekuma North Municipal Health Directorate was notified of a resident who reported to Korle-Bu Teaching Hospital on March 29, 2020 with fever, shortness of breath, general weakness, cough, chest pain. We investigated the report to estimate the magnitude of cases, to determine the secondary infection rate and to institute control and preventive measures.